Spawning grounds model for neotropical potamodromous fishes: conservation and management implications - López-Casas, Silvia; Rogéliz-Prada, Carlos A.; Atencio-García, Victor; Moreno-Árias, Cintia; Arenas, Diana; Rivera-Coley, Kelly; Jimenez-Segura, Luz (Frontiers in Environmental Science, 2025)
IntroductionFreshwater fish migrations are an important natural process. All main river basins in South America have potamodromous fish that migrate upstream to spawn. Therefore, these species withstand fisheries and are socially, economically, and ecologically important. Hydropower dams cause one of the main threats to these fish’s survival. Hydropower is the main source of low-carbon electricity in South America, where the most diverse and endemic riverine fish fauna inhabit. However, hydropower development rarely considers spawning areas or cumulative impacts in fish migratory routes at a macro-basin scale in their environmental impact assessment (EIA) studies. In the present case study conducted in the Magdalena basin in Colombia, a distribution model of potential spawning areas of migratory fish species was developed. The objective of the current research is to demonstrate the potential use of early planning tools at the macro-basin scale to ensure that freshwater ecosystems remain functional in supporting fish migrations.MethodsPotential spawning areas for 15 migratory fish species were determined using ichthyoplankton sampling records, embryonic and larval time development, water velocity, and average flow time estimations. Spawning distribution grounds, analyzed for species diversity and richness, were overlaid with the national hydropower projects portfolio to examine the potential loss of reproduction areas due to hydropower dam development.Results and discussionOur basin-wide model calculated spawning areas for all of the identified species in available ichthyoplankton samples, using available data on the duration for larval and embryonic development. The proposed model estimated the potential impacts of projected hydropower development in the Magdalena basin and revealed spawning grounds encompassing 11,370 km of rivers, spanning Strahler orders three to eight, which represented 11.2% of the entire river network. These areas overlapped with 80 hydropower projects (56.7% of the total), with a projected 45.0% loss experienced in reproduction areas for potamodromous species.ConclusionManagement measures to promote freshwater fish species conservation must avoid river fragmentation and critical habitat loss, while promoting habitat connectivity. This model provides a solution to analyze fragmentation impacts from hydropower dam development in data-limited basins. It supports science-based decision-making for choosing dam location arrangements that minimize impacts (connectivity and reproductive habitat loss), while ensuring that rivers continue to support migratory fish for better conservation and food security outcomes.